Analisis Congestion Faktor Pada Logistik Alkes dan Obat Rumah Sakit Muhammadiyah Dengan Analytical Hierarchy Process - Abdurrahman Faris Indriya Himawan; Efta Dhartikasari Priyana; Mohamad Hazeem bin Mohmad Sidik (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background – Suppliers are business partners who play a significant role in ensuring the availability of supply goods needed by the company. Supplier performance will affect the company's performance; therefore companies need to assess suppliers carefully and sustainably. Supplier assessments should be based on criteria that add current value and future value. Aim – This study aims to select the best suppliers in supplying drug and medical devices in hospitals. Design / methodology / approach – This research approach is quantitative by using Analytical Hierarchy Process (AHP) analysis in determining the best quality weight to be selected by Muhammadiyah Hospital based on five criteria, namely price, quality, service, accuracy of delivery, and accuracy of quantity. Findings – Based on the calculation results using the Analytical Hierarchy Process (AHP) method, the criteria that got the highest weight were quality with a weight of 0.44, the second order was the price with a weight of 0.34, the third order was the service with a weight of 0.13, the fourth order was the accuracy of delivery with a weight of 0.05, and the last was delivery with a weight of 0.03. While the order of suppliers that get the highest weight is PT. X with a weight of 0.38, the second is PT. Y with a weight of 0.36 and the last one PT. Y with a weight of 0.09. Research implication – Some things that are considered in choosing a supplier are delivery, quality, service, past performance, payment. The goal is none other than to know the best suppliers of hospitals. Limitations – This research has a limit on the number of cases of hospitals managed by Muhammadiyah, it is still very likely to be developed for other government or private hospitals or health clinics.